ANALISIS PERBEDAAN TINGKAT KONSERVATISME SEBELUM DAN SESUDAH KONVERGENSI IFRS PADA PERUSAHAAN PROPERTI, REAL ESTAT, DAN KONSTRUKSI DI BURSA EFEK INDONESIA - Gunawan, Listiarini; Lindrawati, Lindrawati (Jurnal Akuntansi Kontemporer, 2016)
The company, which is listed on the Indonesia Stock Exchange (IDX), are required to prepare financial statements based on accounting principles contained in the conceptual framework. One of the principles used is accounting conservatism. Before the convergence of IFRS, the measurement elements of financial statements based on historical cost, where the cost of that happened in the past is used as the basis for the present recording. After convergence of IFRS, these measurements changed using professional judgment in which the assessment is more optimistic because the company may recognize changes in the value of an element of financial statements in accordance with fair value. Therefore, this study aimed to analyze the differences in the level of conserva-tism before and after the convergence of IFRS on company property, real estate, and construction in the period 2006-2007 and 2012-2013 which is listed on the IDX. The results showed that there was no difference in the level of conservatism before and after IFRS convergence. IFRS allows companies to keep using conservatism if the method can produce the best information that can be achieved by the company. Currently the company is in a situation of high uncertainty, the company will tend to be more conserva-tive. Conservatism is also considered to be able to resolve agency problems that occur, namely the existence of information asym-metry in the preparation of financial statements that give rise to opportunities for companies to manage earnings